High posterior cerebral artery flow predicts ischemia recurrence in patients with internal carotid artery occlusion - Jud, Simon; Klövekorn, Robert; van Niftrik, Christiaan Hendrik Bas; Herzog, Lisa; Sebök, Martina; Schweizer, Juliane; Luft, Andreas R.; Fierstra, Jorn; Wegener, Susanne (Frontiers in Neurology, 2023)
Recurrent stroke is a dreaded complication of symptomatic internal carotid artery occlusion (ICAO). Transcranial Duplex (TCD)-derived increased flow velocity in the ipsilateral posterior cerebral artery (PCA)-P2 segment indicates activated leptomeningeal collateral recruitment and hemodynamic impairment. Leptomeningeal collaterals are pial vascular connections between the anterior and posterior vascular territories. These secondary collateral routes are activated when primary collaterals via the Circle of Willis are insufficient. Our goal was to test the TCD parameter PCA-P2 flow for prediction of ipsilateral ischemia recurrence. We retrospectively analyzed clinical and ultrasound parameters in patients with ICAO. Together with clinical variables, we tested systolic PCA-P2 flow velocity as predictor of a recurrent ischemic event using logistic regression models.Of 111 patients, 13 showed a recurrent ischemic event within the same vascular territory.Increased flow in the ipsilateral PCA-P2 on transcranial ultrasound (median and interquartile range [IQR]: 60cm/s [IQR 26] vs. 86cm/s [IQR 41], p = <0.001), as well as previous transient ischemic attack (TIA) and low NIHSS were associated with ischemia recurrence. Combined into one model, accuracy of these parameters to predict recurrent ischemia was 89.2%.Our data suggest that in patients with symptomatic ICAO, flow increases in the ipsilateral PCA-P2 suggest intensified compensatory efforts when other collaterals are insufficient. Together with the clinical variables, this non-invasive and easily assessable duplex parameter detects ICAO patients at particular risk of recurrent ischemia.